The Biology of Invasive Native Plant as an Ex-situ Collection: A Case Study of Epipremnum pinnatum (L.) Engl. (Araceae) in Bogor Botanical Garden, Indonesia - zulkarnaen, rizmoon; Martiansyah, Irfan; Damayanti, Frisca; Wardani, Fitri Fatma; Yudaputra, Angga; Robiansyah, Iyan; Hutabarat, Prima Wahyu K.; Harto, Harto (Jurnal Riset Biologi dan Aplikasinya, 2024)
The Bogor Botanical Garden (BBG) is a pivotal center for plant research and conservation, boasting a diverse collection of over 12,000 individual plants spanning various species. However, among the plant collections at BBG, some of them have the potential to be invasive. Therefore, this study aimed to uncover the plant collections at BBG with invasive potential and analyze the distribution of one of the most dominant collections, Epipremnum pinnatum (L.) Engl. The method employed in this research involved a literature review to identify which plant collections have invasive potential and a vegetation analysis on the distribution of E. pinnatum within BBG. Additionally, ANOVA analysis and regression models were employed to explore the relationship between environmental factors and E. pinnatum abundance. Results revealed that BBG hosted 78 potentially invasive plant species, with E. pinnatum comprising 28 individuals. Spatial analysis indicates a clustered distribution of E. pinnatum, influenced by seed dispersal mechanisms, environmental factors, and biotic interactions. Correlation analysis links soil pH, soil moisture, and canopy cover to E. pinnatum distribution. Canopy cover demonstrates a significant positive correlation with E. pinnatum abundance, suggesting its importance in providing favorable microclimates for growth. Regression analysis further supports canopy cover as a predictor of E. pinnatum presence. However, while a strong statistical association was observed, causal relationships require further investigation. This study underscores the complexity of ecological dynamics in BBG and emphasizes the need for comprehensive research to define underlying mechanisms driving plant distributions and interactions.